- Urgensi Pemikiran Filsafat: Urgensi Pemikiran Filsafat - Nurdiansyah, Putra Pandu Dinata; Mubaraq, Zulfi; Hakim, Muhammad Aunul; SJ, Fadil (Jurnal Filsafat Indonesia, 2025)
This article raises the importance of philosophical thinking by focusing on three main things: the paradigm of the urgency of philosophical thinking, the internal and external factors that influence it, and its positive and negative implications for Muslim thinking. The research method used is library research with a text approach based on literature theory. Data collection is done through collection, selection, classification, and analyzed with qualitative data analysis techniques of Miles and Huberman models. The results of the study show that the urgency paradigm of philosophical thinking has three forms: as a critical dialog partner, as a parent of science, and as an insight enhancer. Internal factors that influence the urgency of philosophical thinking include human curiosity, human awe of the universe, and thinkers' dissatisfaction with existing answers. External factors include freedom of thought, research into the origin of nature, and the influence of myths and fables in the Greek belief system. The positive implications of the urgency of philosophical thinking on Muslim thought include being a guide to scientific issues, a compass for the development of knowledge, and a means of testing scientific reasoning. However, there are also negative implications such as the emergence of nihilism, uncertainty, and lack of concern for practical or empirical aspects. In conclusion, the paper emphasizes that philosophy has an important role in various aspects of people's lives. In understanding nature, values, and actions, philosophy helps shape the way we understand the origins of knowledge. It also plays a key role in the development of science, ethics, politics, culture, and enriches our understanding of the meaning and purpose of life.